The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1063/1.4819142
|View full text |Cite
|
Sign up to set email alerts
|

A non-discrete method for computation of residence time in fluid mechanics simulations

Abstract: Cardiovascular simulations provide a promising means to predict risk of thrombosis in grafts, devices, and surgical anatomies in adult and pediatric patients. Although the pathways for platelet activation and clot formation are not yet fully understood, recent findings suggest that thrombosis risk is increased in regions of flow recirculation and high residence time (RT). Current approaches for calculating RT are typically based on releasing a finite number of Lagrangian particles into the flow field and calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 46 publications
(55 reference statements)
2
59
0
Order By: Relevance
“…Using a Lagrangian approach, T R evolution can be described by the advection equation with unit forcing, tTR+·false(υincTRfalse)=1, where υinc is the velocity field. Previous works have considered a similar equation with a non-zero mass diffusivity term (Esmaily-Moghadam et al 2013, Jozsa & Kramer 2000, Mangual et al 2012), but we note that the self-diffusivity of blood is negligible compared to its advective fluxes inside the LV (Bermejo et al 2015, Tarbell 2003). The full derivation of equation (1) can be found in Appendix I.…”
Section: Methodsmentioning
confidence: 90%
“…Using a Lagrangian approach, T R evolution can be described by the advection equation with unit forcing, tTR+·false(υincTRfalse)=1, where υinc is the velocity field. Previous works have considered a similar equation with a non-zero mass diffusivity term (Esmaily-Moghadam et al 2013, Jozsa & Kramer 2000, Mangual et al 2012), but we note that the self-diffusivity of blood is negligible compared to its advective fluxes inside the LV (Bermejo et al 2015, Tarbell 2003). The full derivation of equation (1) can be found in Appendix I.…”
Section: Methodsmentioning
confidence: 90%
“…This work incorporates recent advances in simulation technology, including lumped parameter boundary conditions (Lagana et al 2002), increasing anatomical realism, particle tracking (Shadden and Taylor 2008), and non-discrete residence time computations (Esmaily-Moghadam et al 2013). In addition, we also make a direct comparison between simulations with rigid and deformable walls to quantify the resulting differences in wall shear stress (WSS) (Figueroa et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies simulating flow conditions in KD have recently shown that these hemodynamic factors may be better predictors of thrombotic risk than aneurysm diameter alone. 4,32 However, validation of simulations in realistic coronary aneurysm geometries with physiologic flow conditions has not been previously performed. Validation is key to supporting the continued development of CFD tools in support of KD patient management.…”
Section: Discussionmentioning
confidence: 99%